2022
DOI: 10.1186/s12876-022-02133-z
|View full text |Cite
|
Sign up to set email alerts
|

Graves’ disease overlapping with chronic hepatitis B and methimazole-induced liver injury and autoimmune hepatitis: a case report

Abstract: Background Liver injury related to Graves’ Disease (GD) includes hepatotoxicity of thyroid hormone excess, drug-induced liver injury, and changes resulting from concomitant liver disease. Methimazole (MMI) has been shown to induce several patterns of liver injury. However, the diagnosis and treatment of autoimmune hepatitis (AIH) overlapping with either GD or chronic hepatitis B are challenging. Case presentation A 35-year-old man from China presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
0
0
Order By: Relevance
“…Although adverse reactions of MMI are more dose-dependent rather than idiosyncratic, a small number studies showed patients who developed MMI-induced hepatotoxicity had good response to glucocorticoid therapy, indicating an allergic reaction to MMI. [12] In our patient, her cholestatic jaundice was rapidly recovered after about 3-month glucocorticoid therapy without recurrence during a 6-month follow-up, supporting the above findings. Of course, we could not totally ignore the effects of other comprehensive treatment, such as liver-protecting therapy and blood glucose control.…”
Section: Discussionsupporting
confidence: 88%
“…Although adverse reactions of MMI are more dose-dependent rather than idiosyncratic, a small number studies showed patients who developed MMI-induced hepatotoxicity had good response to glucocorticoid therapy, indicating an allergic reaction to MMI. [12] In our patient, her cholestatic jaundice was rapidly recovered after about 3-month glucocorticoid therapy without recurrence during a 6-month follow-up, supporting the above findings. Of course, we could not totally ignore the effects of other comprehensive treatment, such as liver-protecting therapy and blood glucose control.…”
Section: Discussionsupporting
confidence: 88%
“… 156 , 157 Although most patients have mild hepatic impairment, a minority may develop life-threatening conditions owing to severe liver injury. 158 , 159 Studies on the incidence and severity of drug-induced liver injury caused by methimazole and propylthiouracil are not entirely consistent. Wang et al 160 retrospectively analyzed 71,379 patients treated with antithyroid medications in Taiwan from 2004 to 2008, and indicated that the incidence of drug-induced liver injury caused by methimazole was higher than that of propylthiouracil, and correlated with the dose of methimazole, but the occurrence of acute hepatic necrosis and cholestasis was similar to that of propylthiouracil.…”
Section: Common Liver Injury–causing Drugs Linked To Gut Microbiotamentioning
confidence: 99%